Where to invest in neonatal survival programs in Nepal? A modelling study using Lives Saved Tool through scaling key interventions - Geha Nath Khanal; Nisha Giri; Deepak Jha; Dipak Raj Chaulagain (PLoS ONE, 2025)
Background Neonatal survival remains a major public health priority in many low and middle-income countries including Nepal, where the neonatal mortality rate (NMR) is 21 per 1,000 live births. To improve the neonatal health outcomes, the World Health Organization (WHO) recommends scaling up coverage of quality antenatal care (ANC), skilled care at birth, immediate essential newborn care and resuscitation, postnatal care for mother and newborn, and specialized care of small and sick newborns. In this context, we aimed to estimate the potential impact of achieving the coverage targets for 35 interventions, identified as monitoring indicators under Nepal’s Every Newborn Action Plan (NENAP), on neonatal survival in Nepal by 2035. Methods We used the Lives Saved Tool (LiST) to estimate the number of neonatal deaths that could be prevented by 2035 if target intervention coverage level is achieved, starting from 2025 baseline values. Baseline data were drawn from demographic and health (DHS) survey and multiple indicator cluster survey (MICS). Where survey data were unavailable, proxy estimates were derived from available literatures to establish the baseline levels. Results By 2035, achieving the target coverage level could save an estimated 8,126 neonatal lives compared to the 2025 baseline. This achievement would reduce the NMR to about 14 per 1,000 live births and avert an additional 5,977 child deaths and 358 maternal deaths. More than two-third (70.4%) of neonatal lives saved would be attributable to four priority interventions: neonatal resuscitation (36.0%), promotion of breastfeeding practices (11.8%), case management of neonatal sepsis (11.7%) and case management of premature babies (10.9%). At this coverage level, approximately 26.9% of deaths due to prematurity, 17.9% from sepsis, and 16.1% from diarrhoea could be prevented. Conclusion Nepal must prioritize highly effective interventions: neonatal resuscitation, breastfeeding, management of neonatal sepsis and case management of premature babies to accelerate progress towards the NENAP target. Our analysis indicates that achieving the specific coverage targets of 35 NENAP interventions could reduce the NMR to 14 per 1,000 live births which fall short of the NENAP targets of reducing NMR to 11 per 1,000 live births by 2035. Strengthening special newborn care unit (SNCU) in line with WHO standard is critical to improving the quality of care for small and sick newborns (SSNB) in health facilities. While strengthening newborn resuscitation and SNCU services will substantially reduce NMR, attaining the NENAP targets will ultimately require comprehensive health system reforms and effective coverage of other maternal and newborn interventions.